The social construction of the humanitarian health drone: socialising the UAV - Castellon, Alexandre (Unpublished, 2020)
As unmanned aerial vehicles become increasingly present across everyday domains and lives, understanding the social factors driving and shaping the form of these machines gains in urgency. Inspired by socio-philosophical frameworks, this thesis seeks to determine the social drivers and outcomes of this technology, exploring humanitarian health applications in added depth as an empirical example from which future research can derive. A discourse analysis explores recurring themes and phrases from primary and secondary sources which participate in the construction of drone-related narratives, which through the eye of visions and Utopianism can be seen to promote pro-drone conceptualisations of the future. This piece concludes that using a ‘visions’ framework may help frame narratives and guide balanced and considered regulation for the future.